The fundamentals of software aging - Grottke, Michael; Matias, Rivalino; Trivedi, Kishor (1st International Workshop on Software Aging and Rejuvenation/19th IEEE International Symposium on Software Reliability Engineering, 2008)
Since the notion of software aging was introduced thirteen years ago, the interest in this phenomenon has been increasing from both academia and industry. The majority of the research efforts in studying software aging have focused on understanding its effects theoretically and empirically. However, conceptual aspects related to the foundation of this phenomenon have not been covered in the literature. This paper discusses foundational aspects of the software aging phenomenon, introducing new concepts and interconnecting them with the current body of knowledge, in order to compose a base taxonomy for the software aging research. Three real case studies are presented with the purpose of exemplifying many of the concepts discusse
WiSo-Import:2015-04-17:1484
Keywords: Innovation